Acute Lumbar Burst Fracture Treated by Minimally Invasive Lateral Corpectomy - Rodrigo Amaral; Luis Marchi; Leonardo Oliveira; Thiago Coutinho; Luiz Pimenta (Case Reports in Orthopedics)
Burst fractures in acute spinal traumas are a difficult problem to solve. Different approaches and techniques have been utilized, but with high incidence of morbidity and mortality, besides unsatisfactory clinical and radiological results. Mini-open approaches recently emerged and have been shown to be safe and effective in the treatment of several spinal conditions. Here we report a case of acute lumbar burst fracture at L2 treated by minimally invasive true lateral approach posteriorly instrumented with percutaneous pedicle screws. The minimum disruptive access in addition to a rigid construction allowed a lumbar corpectomy without the morbidity of standard open approaches, lowering surgery costs and accelerating the patient recovery with successfully clinical and radiological results.